(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This study examines the level of utilization of digital platforms and e-commerce systems by small businesses and evaluates their impact on economic efficiency. In the context of the modern digital economy, small and medium-sized enterprises increasingly adopt digital technologies such as online marketplaces, social media marketing tools, cloud-based accounting systems, digital payment solutions, and logistics management platforms to improve their operational performance. The research highlights that the integration of digital platforms enables small businesses to automate business processes, reduce operational costs, expand market access, and strengthen customer engagement. The study also identifies key factors influencing the adoption of digital technologies, including technological readiness, digital literacy, financial resources, and institutional support. It is revealed that businesses operating in urban areas tend to adopt digital tools more rapidly due to better infrastructure and access to technological services, while rural enterprises face challenges related to limited internet access and insufficient digital skills. Furthermore, the research demonstrates that digital payments, data analytics, and e-commerce platforms significantly enhance transaction efficiency, decision-making processes, and market competitiveness.